Partnership principles in a teacher coaching programme - Zubaidah Bibi Mobarak Ali; Hamidah Yamat; Wahiza Wahi (Penerbit Universiti Kebangsaan Malaysia, 2022)
Research provides strong support for the promise of teacher coaching programme in redesigning teachers’ instructional practices that enhance students’ learning. Informed by Knight’s (2007) partnership coaching principles, this paper reports on a study on teacher coaching programme in Malaysia, particularly involving teacher coaches, known as School Improvement Specialist Coaches Plus (SISC+). This case study disclosed the partnership principles applied by an SISC+ with three of her coached English Language (EL) teachers and how these principles were being exercised in a suburban school, and how the principles achieved collaborative teacher-SISC+ alliance. Data were drawn from observations and interviews conducted with the SISC+ and the coached teachers. The data were analysed thematically. Findings revealed that the SISC+ effectively utilised the principles, and by doing so, she was able to collaborate with the teachers and support their learning. The findings implicate that these principles must be learnt and understood by all the SISC+ as basic of coaching in obtaining teacher acceptance, build teacher-SISC+ collaborative relationships and support required changes in teachers’ instructional practices and that will bring about astounding students’ outcome.